Breast Cancer Treatment in Balb/C Mice Using Dendritic Cells - Nowruz Delirezh; Akram Zangeneh; Sanaz Sheikhzadeh; Naser Abbasi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām)
Introduction:  A fourth of all cancers in women in the country are breast cancer, making it the most common and fatal cancer in women. Some novel approaches are being implemented to reduce the impact of cancer. Thus, this study was conducted to treat breast cancer using dendritic cells in mice. Materials & Methods: The study used the 4T1 cell line to induce breast cancer in Balb/C mice. After tumor induction, the mice were divided into three groups: healthy control, tumor control, and dendritic cell-treated groups. After developing palpable tumors, each group was treated with one million dendritic cells twice at a two-week interval. Body weight, tumor weight, and breast tissue samples were taken for pathological examination. Cells were photographed during the 9-day dendritic cell culture period. One-way analysis of variance (ANOVA) and Duncan's test were used in SPSS V.24 to analyze the data at the 0.05 significance level. Results: In the dendritic cell treatment group, the ratio of tumor weight to body weight went down, and the amount of tumor weight loss was balanced out compared to the tumor control group. The dendritic cell receiving group also had a lot more tumor growth inhibition. The dendritic cell-treated group showed an increase in the number of immune cells in the tumor tissue. Conclusion: Treatment with dendritic cells for the treatment of breast tumors enhances the immune response against the tumor.